Rhodotorula sp.–based biorefinery: a source of valuable biomolecules - Mussagy, Cassamo U.; Ribeiro, Helena F.; Santos-Ebinuma, Valeria C. [UNESP]; Schuur, Boelo; Pereira, Jorge F. B. (Springer Nature, 2022)
Abstract: The development of an effective, realistic, and sustainable microbial biorefinery depends on several factors, including as one of the key aspects an adequate selection of microbial strain. The oleaginous red yeast Rhodotorula sp. has been studied as one powerful source for a plethora of high added-value biomolecules, such as carotenoids, lipids, and enzymes. Although known for over a century, the use of Rhodotorula sp. as resource for valuable products has not yet commercialized. Current interests for Rhodotorula sp. yeast have sparked from its high nutritional versatility and ability to convert agro-food residues into added-value biomolecules, two attractive characteristics for designing new biorefineries. In addition, as for other yeast-based bioprocesses, the overall process sustainability can be maximized by a proper integration with subsequent downstream processing stages, for example, by using eco-friendly solvents for the recovery of intracellular products from yeast biomass. This review intends to reflect on the current state of the art of microbial bioprocesses using Rhodotorula species. Therefore, we will provide an analysis of bioproduction performance with some insights regarding downstream separation steps for the extraction of high added-value biomolecules (specifically using efficient and sustainable platforms), providing information regarding the potential applications of biomolecules produced by Rhodotorula sp, as well as detailing the strengths and limitations of yeast-based biorefinery approaches. Novel genetic engineering technologies are further discussed, indicating some directions on their possible use for maximizing the potential of Rhodotorula sp. as cell factories. Key points: • Rhodotorula sp. are valuable source of high value-added compounds. • Potential of employing Rhodotorula sp. in a multiple product biorefinery. • Future perspectives in the biorefining of Rhodotorula sp. were discussed.
Keywords: Biorefinery; Carotenoids; Enzymes, Circular bioeconomy; Lipids; Rhodotorula; Yeast